Contactless Braille sensing based on GaN optical devices integrated with epoxy lenses - Hongyu Cheng; Jiahao Yin; Sirui Li; Kwai Hei Li (Microsystems & Nanoengineering)
Abstract Braille serves as an efficient means for visually impaired individuals to access textual information and engage in communication. However, the process of reading Braille can often be cumbersome and time-intensive, particularly in bidirectional human-machine interaction. In this work, a compact optical device for contactless detection of Braille is fabricated and characterized. The GaN-on-sapphire chip, which employs monolithic integration, serves as the core for both light emission and photodetection, significantly reducing its overall footprint. The incorporation of the semi-ellipsoid epoxy lens with optimized dimensions ensures consistent and accurate detection. The sensing device demonstrates high stability and fast response through its line-scanning capabilities on Braille codes. The captured signals are analyzed using a microcontroller, and the Braille recognition results are wirelessly transmitted to a portable mobile device, enabling the conversion into audio and visual formats. This innovative design not only facilitates Braille reading but also holds the potential to advance human-machine interaction.